Detection of Equine Herpesvirus Infection : Conventional Versus Molecular Approaches - N. F. Abdullah; N. E. M. Redhuan; M. Mohamed; Nur Hardy Abu Daud; B. Zeshan (Pakistan Agricultural Scientists Forum (PAS FORUM), 2018)
Equine herpesvirus (EHV) are the highly contagious pathogens that infect both domestic and wild equine populations causing a major impact on equine industry worldwide. The methods for diagnosis of EHV have shown a vast improvement in the last decade. Although some conventional techniques are still applicable in certain cases, most of the clinical testing now focusing on rapid diagnosis by using the nucleic acid amplification-based techniques as major advances for the detection of EHV. The diagnosis of EHV does not only depend on clinical situation alone, but the suitability of diagnostic test is also vital for equine clinicians to make a decision regarding the specific treatments and control measures to be taken. Therefore, crucial understanding of the strengths and limitations of each assay are needed in order to interpret the results. Realizing the issue, this review intends to outline the clinical application of conventional approaches and the progress of the new molecular approaches. Relative advantages and limitations of each method have also been discussed.